Development and characterization of attenuated metabolic mutants of Bordetella bronchiseptica for applications in vaccinology. (7th June 2012) - Yevsa, Tetyana; Ebensen, Thomas; Fuchs, Barbara; Zygmunt, Beata; Libanova, Rimma; Gross, Roy; Schulze, Kai; Guzmán, Carlos A.
Summary: Bordetella bronchiseptica is an important pathogen causing a number of veterinary respiratory syndromes in agriculturally important and food‐producing confinement‐reared animals, resulting in great economic losses annually amounting to billions of euros worldwide. Currently available live vaccines are incompletely satisfactory in terms of efficacy and safety. An efficient vaccine for livestock animals would allow reducing the application of antibiotics, thereby preventing the massive release of pharmaceuticals into the environment. Here, we describe two new potential vaccine strains based on the BB7865 strain. Two independent attenuating mutations were incorporated by homologous recombination in order to make negligible the risk of recombination and subsequent reversion to the virulent phenotype. The mutations are critical for bacterial metabolism, resistance to oxidative stress, intracellular survival and in vivo persistence. The resulting double mutants BB7865 risA aroA and BB7865 risA dapE were characterized as promising vaccine candidates, which are able to confer protection against colonization of the lower respiratory tract after sublethal challenge with the wild‐type strain.